DisastDrone: A Disaster Aware Consumer Internet of Drone Things System in Ultra-Low Latent 6G Network - Mukherjee, Amartya; De, Debashis; Dey, Nilanjan; González-Crespo, Rubén; Herrera-Viedma, Enrique (IEEE Transactions on Consumer Electronics, 2023)
Internet of Things application in disaster responses and management is a predominant research domain. The introduction of the consumer drones, flying ad-hoc networks, low latency 5G, and beyond 5G produce significant acceleration of this research. The work proposed the implementation of the Consumer Internet of Drone Things (CIoDT) framework for emergency message transfer among smart grid systems and other power sources and enables stable network connectivity in a disaster scenario. A real-life mobility model has been engineered, and the edge-enabled opportunistic MQTT message transfer mechanism is implemented. Also, a dedicated network slice is devised to examine routing performance. A real-life prototype test-bed emulator has been designed to evaluate mobility, message delivery, and flight attitude performance. The results show a message delivery probability of nearly 0.99 in Quality of Service 2(QoS2), and 1.19 seconds of end-to-end latency in Quality of Service level 1(QoS1). An experiment also shows a 94% of coverage ratio in a network slice for QoS2, 84% of bandwidth utilization per network slice, and a minimum of 100ms latency per network slice. The proposed system is highly suitable for mass production of light weight drone network for disaster management.
Keywords: 6G-slice; CIoDT; cluster mobility; disaster management; map-based waypoint mobility; smart grid; Scopus; JCR